The adhesion receptor GPR56 is activated by extracellular matrix collagen III to improve β-cell function - Olaniru, Oladapo E. (Cell Mol Life Sci, 2018)
AIMS: G-protein coupled receptor 56 (GPR56) is the most abundant islet-expressed G-protein coupled receptor, suggesting a potential role in islet function. This study evaluated islet expression of GPR56 and its endogenous ligand collagen III, and their effects on β-cell function. METHODS: GPR56 and collagen III expression in mouse and human pancreas sections was determined by fluorescence immunohistochemistry. Effects of collagen III on β-cell proliferation, apoptosis, intracellular calcium ([Ca(2+)](i)) and insulin secretion were determined by cellular BrdU incorporation, caspase 3/7 activities, microfluorimetry and radioimmunoassay, respectively. The role of GPR56 in islet vascularisation and innervation was evaluated by immunohistochemical staining for CD31 and TUJ1, respectively, in pancreases from wildtype (WT) and Gpr56(−/−) mice, and the requirement of GPR56 for normal glucose homeostasis was determined by glucose tolerance tests in WT and Gpr56(−/−) mice. RESULTS: Immunostaining of mouse and human pancreases revealed that GPR56 was expressed by islet β-cells while collagen III was confined to the peri-islet basement membrane and islet capillaries. Collagen III protected β-cells from cytokine-induced apoptosis, triggered increases in [Ca(2+)](i) and potentiated glucose-induced insulin secretion from WT islets but not from Gpr56(−/−) islets. Deletion of GPR56 did not affect glucose-induced insulin secretion in vitro and it did not impair glucose tolerance in adult mice. GPR56 was not required for normal islet vascularisation or innervation. CONCLUSION: We have demonstrated that collagen III improves islet function by increasing insulin secretion and protecting against apoptosis. Our data suggest that collagen III may be effective in optimising islet function to improve islet transplantation outcomes, and GPR56 may be a target for the treatment of type 2 diabetes. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00018-018-2846-4) contains supplementary material, which is available to authorized users.